Tufts men's tennis team on court - Unknown (Tufts Archival Research Center, 2008)
7.5 x 9.5; date approximate. [Possibly identified as: Crowell (coach), Whittaker, Claus, Hathaway, Walker (capt.), Pear, Sheinberg, Kavanaugh, Pring (mgr.)]